TECHNIQUE, IMAGINARY AND SAMBA – THE INFLUENCE OF ARTIFICIAL INTELLIGENCE IN BRAZILIAN CARNIVAL, 2025 - da Costa, Andriolli de Brites; Martins, Thales (AoIR Selected Papers of Internet Research, 2026)
This work seeks to survey the ways in which artificial intelligence has affected Brazilian carnival, especially that of samba schools in Rio de Janeiro and São Paulo and its cultural environment. This survey will serve as the basis for a cultural critique that will reflect on the ways in which this imaginary of technique, which imputes to us an almost Faustian urgency of efficiency, productivity, speed and future, affects a cultural manifestation marked by social criticism, revolution and appreciation of community and artisanal work.The basis for this criticism is the theory of archetypological imagery, which is that this epitome of technique is a demarcation of Western ways of feeling, thinking and acting since the 19th century (Durand, 2012). The reasoning is complemented by questions from Neil Postman, for whom the relentless advancement of technology harms the preservation of traditions, impacting mental processes and social relations in a community (1994, p. 12). Far from seeking an apocalyptic alignment that rejects technological transformations, we understand that popular festivals are characterized by social dynamism. However, by questioning the way in which these adherences have been made in an unreflective way, we hope to collaborate with critical thinking and complex reflection on a phenomenon that will affect our own way of relating to tradition.